ECOLOGICAL DISHARMONY AS THE SIN AGAINST THE SPIRIT - Williams, David T. (Scriptura, 2013)
Although it is widely accepted that human activity is the cause of many of the ecological problems that are becoming increasingly evident, such activity is generally not really considered as morally wrong. Even less, although it may be seen as damaging a creation originally made good, is it seen as a sin against God. However, sin against the environment is certainly serious, and can even be seen as a sin against the Spirit. This is because the Spirit may be seen as the source of the harmony that is characteristic of biodiversity, and related to this, the source of the inter-relatedness within every organism that is the essence of life. The possibility is that extinction of species will continue, and even that life itself will end. This would indeed be a sin against the Spirit, a sin described appropriately in the Bible as ‘mortal’ (1 Jn. 5:16). It is a negation of the human role in the creation as in imago Dei. Hope lies in that while sin against the Spirit is unforgivable (e.g. Matt 12:32), this refers not to an isolated fault but an ongoing persistent attitude, which then can be reversed, motivating willingness to act as in priestly capacity as agents of the Spirit to give environmental healing. Just as physical healing in the body, this is a restoration of the harmony intended by the Spirit, and is often by the application of the laws that are part of the created order. As with sanctification, this is a foretaste of the perfection that God promises in the creation of a new environment.